Mexico : Technical Assistance for Long-term Program of Renewable Energy Development - Antonius, Andrés (World Bank, Washington, DC, 2014)
The four studies in this technical paper series deal with complementary themes and propose solutions to the same problems that all of them perceive in the Mexican electricity sector - yet each paper looks at the problem from a different angle, and proposes different actions that must be taken in order to bring about a significant increase in Mexico's adoption of on-grid renewable energy. These papers take us from the general overview of the policy and institutional context, down to the specific case of a hypothetical wind farm. They review the current situation, identify concrete policy and institutional changes that are badly needed to stimulate the sector, look at how new paradigms for valuation can help us to better account for the value of renewable energy capacity, and finally perform a thorough economic impact analysis of the hypothetical addition of a large wind farm to Mexico's grid.